Validation of a five-level triage system in pediatric trauma and the effectiveness of triage nurse modification: A multi-center cohort analysis - Liu, Tien-Tien; Cheng, Chi-Tung; Hsu, Chih-Po; Chaou, Chung-Hsien; Ng, Chip-Jin; Jeng, Mei-Jy; Chang, Yu-Che (Frontiers in Medicine, 2022)
Abstract Introduction: Triage is one of the most important tasks for nurses in a modern emergency department (ED) and it plays a critical role in pediatric trauma. An appropriate triage system can improve patient outcomes and decrease resource wasting. However, triage systems for pediatric trauma have not been validated worldwide. To ensure clinical reliability, nurses are allowed to override the acuity level at the end of the routine triage process. This study aimed to validate the Taiwan Triage and Acuity Scale (TTAS) for pediatric trauma and evaluate the effectiveness of triage nurse modification. Methods: This was a multicenter retrospective cohort study analyzing triage data of all pediatric trauma patients who visited six EDs across Taiwan from 2015 to 2019. Each patient was triaged by a well-trained nurse and assigned an acuity level. Triage nurses can modify their acuity based on their professional judgment. The primary outcome was the predictive performance of TTAS for pediatric trauma, including hospitalization, ED length of stay, emergency surgery, and costs. The secondary outcome was the accuracy of nurse modification and the contributing factors. Multivariate regression was used for data analysis. The Akaike information criterion and C-statistics were utilized to measure the prediction performance of TTAS. Results: In total, 45,364 pediatric patients were included in this study. Overall mortality, hospitalization, and emergency surgery rates were 0.17%, 5.4%, and 0.76%, respectively. In almost all cases (97.48%), the triage nurses agreed upon the original scale. All major outcomes showed a significant positive correlation with the upgrade of acuity levels in TTAS in pediatric trauma patients. After nurse modification, the Akaike information criterion decreased and C-statistics increased, indicating better prediction performance. The factors contributing to this modification were being under six years of age, heart rate, respiratory rate, and primary location of injuries. Conclusion: The TTAS is a reliable triage tool for pediatric trauma patients. Modification by well-experienced triage nurses can enhance its prediction performance. Younger age, heart rate, respiratory rate, and primary location of injuries contributed to modifications of the triage nurse. Further external validation is required to determine its role in pediatric trauma worldwide.